2005
DOI: 10.1007/s11243-005-6228-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Dissociation of tris-{3-(2-pyridyl)-5,6-bis(2-furyl)-1,2,4-triazine}iron(II)

Abstract: The kinetics of base hydrolysis of the low-spin iron(II)-diimine complex [Fe(fertri) 3 ] 2+ , where fertri=3-(2-pyridyl)-5,6-bis(2-furyl)-1,2,4-triazine, as a function of hydroxide concentration, solvent composition (water; aqueous MeOH), and pressure are reported. Rate constants are also reported for dissociation of the [Fe(fertri) 3 ] 2+ cation in 50-64% MeOH, determined from replacement of the fertri ligands by 1,10-phenanthroline. The reactivity of this fertri complex is compared with reactivities of a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, the log b value for the intermediate ternary complex, 15.74, which is greater than that for Fe(TPTZ) 2þ 2 and less than that for Fe(terpy) 2þ 2 , which is also consistent with formation of this intermediate ternary complex. Burgess et al [23] reported the dissociation and base hydrolysis of tris (3-(2-pyridyl)-5,6-bis(2-furyl)-1,2,4triazine)iron(II) in MeOH-water solvent mixtures with a view to compare substitution rates for tris(3-(2-pyridyl)-5,6-bis(5-furyl sulfonic acid)-1,2,4-triazine)iron(II) with those for its non-sulfonated parent. Here also, the base hydrolysis was found to be a fairly rapid two-stage process with the first step requiring stopped-flow techniques, while the second step was amenable to monitoring by conventional spectrophotometry.…”
Section: Associative Pathmentioning
confidence: 99%
“…Furthermore, the log b value for the intermediate ternary complex, 15.74, which is greater than that for Fe(TPTZ) 2þ 2 and less than that for Fe(terpy) 2þ 2 , which is also consistent with formation of this intermediate ternary complex. Burgess et al [23] reported the dissociation and base hydrolysis of tris (3-(2-pyridyl)-5,6-bis(2-furyl)-1,2,4triazine)iron(II) in MeOH-water solvent mixtures with a view to compare substitution rates for tris(3-(2-pyridyl)-5,6-bis(5-furyl sulfonic acid)-1,2,4-triazine)iron(II) with those for its non-sulfonated parent. Here also, the base hydrolysis was found to be a fairly rapid two-stage process with the first step requiring stopped-flow techniques, while the second step was amenable to monitoring by conventional spectrophotometry.…”
Section: Associative Pathmentioning
confidence: 99%
“…The stability constants of the complexes predominant in solution were calculated according to a computerized iterative method of successive approximations. 11,12 The obtained composition and logE n values with standard errors are presented in Table I. The values of the stability constants are relative, since the dissociation of the ligand was not taken into consideration.…”
Section: Composition and Stability Of The Complexesmentioning
confidence: 99%